Improvement of spontaneous locomotor activity with JAK inhibition by JTE-052 in rat adjuvant-induced arthritis. Issue 1 (December 2015) - Tanimoto, Atsuo; Shinozaki, Yuichi; Nozawa, Keisuke; Kimoto, Yukari; Amano, Wataru; Matsuo, Akira; Yamaguchi, Takayuki; Matsushita, Mutsuyoshi
Abstract Background Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to joint destruction, disability, and decreased quality of life (QOL). Inhibition of Janus kinase (JAK) signaling ameliorates articular inflammation and joint destruction in animal models of RA, but its effects on behaviors indicating well-being are poorly understood. In this study, we evaluated the effect of JAK inhibition on spontaneous locomotor activity in rats with adjuvant-induced arthritis, a rodent model of RA. Methods Arthritis was induced in male Lewis rats by a single subcutaneous injection of Freund's complete adjuvant. The novel JAK inhibitor JTE-052 was orally administered for 7 days after the onset of arthritis. Results Induction of arthritis suppressed the spontaneous locomotor activity of the rats. Administration of JTE-052 completely improved the spontaneous locomotor activity, with partial reductions in articular inflammation and joint destruction. Hyperalgesia and motor functions were also improved, but the efficacy was not complete. However, serum interleukin (IL)-6 levels were completely decreased at 4 h after administration of the first dose of JTE-052. Conclusions This study demonstrated that JAK inhibition improved the spontaneous locomotor activity of rats with adjuvant-induced arthritis, in association with amelioration of pain and physical dysfunction as a consequence of suppression of joint inflammation. Moreover, although further studies are needed, there was possible participation of IL-6 downregulation in the improvement of locomotor activity by JAK inhibition.